Scientific Writing 2.0 : a reader and writer's guide 2.0 - Lebrun, Jean-Luc (New York World Scientific, 2011)
The book helps scientists write papers for scientific journals. Using the key parts of typical scientific papers (Title, Abstract, Introduction, Visuals, Structure, and Conclusions), it shows through numerous examples, how to achieve the essential qualities required in scientific writing, namely being clear, concise, convincing, fluid, interesting, and organized.
1 DVD con herramientas compatibles con Mac y PC para examinar escritos
Keywords: Trabajos científicos -- Redacción; Trabajo intelectual -- Metodología